Renegotiation Process of Small and Medium Enterprises (SMEs) in the United States, Mexico, and Canada Agreement - José G. Vargas-Hernández; M. C. Omar C. Vargas-González (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
This paper aims to set some scenarios for small and medium enterprises (SMEs) from a critical analysis of the provisions in the United States, Mexico, and Canada (USMC-TEMEC) renegotiation, its challenges, and opportunities. The critical analysis departs from the questionable position of the withdrawal from USMC-TEMEC and the consequences for SMEs of not giving continuity through a process of renegotiation among the three partners. The method used is the critical analysis based mainly on some sources of information, analysis of results of USMC-TEMEC, and the strategic examination of its challenges and opportunities for SMEs. Finally, the analysis establishes some possible scenarios post-USMC-TEMEC renegotiation and some strategic proposals for the SMEs.